Overtherapy or undertherapy for papillary thyroid microcarcinoma? - Dietlein, M.; Schober, O.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2004)
Papillary thyroid microcarcinomas £1 cm have an excellent prognosis both in terms of overall and relapse-free survival. Their high prevalence in autopsy series suggests that most papillary microcarcinomas do not progress to clinically relevant cancer. The extent of surgery is still controversial. Lobectomy or subtotal resection are standard procedures, but multifocal microcarcinomas or lymph node metastases might be overlooked. The pros and cons of completion thyroidectomy and ablative radioiodine therapy are based on limited evidence due to heterogenous inclusion criteria in published series. The retrospective data analyses included subgroups with infiltration of the thyroid capsule, lymph node metastases or multifocal microcarcinomas at the primary staging. The local relapse rate reached approximately 7% after different therapeutic regimes. Radioiodine ablation decreased the recurrence rate in some retrospective studies, but data are inconsistent. Successful radioiodine ablation is possible also after less radical surgery without complete thyroidectomy with postoperative 131I uptake of 10 to 20% or remnants of 3-8 ml. This concept was evaluated successfully in a monocentric series of patients with multifocal microcarcinomas. The therapeutic consideration should include the diameter of the carcinoma, neigh-bourhood to the thyroid capsule, histopathologic subgroups, age, familiar occurrence, patient’s informed consent and in future moleculargenetic tests, too. Therefore, limited surgical procedures for small papillary carcinomas as therapeutic standard, respectively thyroidectomy, lymph node dissection in the central compartment of the neck and ablative radioiodine therapy for individual cases are options for experienced surgeons and specialized tumour centers.
Keywords: Microcarcinomas; thyroid cancer; radioiodine therapy